Sleep-Wake dilemma in future generation Health Care Providers: A cross-sectional analysis - Singhal, Bandini; Shikha, Deep; Das, Sai Chandan; Sinha, Richa; Juyal, Ruchi; Kaur, Gagandeep (Indian Journal of Community Health, 2024)
Introduction: Medical students are at higher risk for sleep disorders due to academic workload, stress, and mental health issues. This study evaluates sleep disorders and their contributing factors. Material and methods: It was a cross sectional study with a sample size of 255 respondents. Collection of demographic information, Socio-economic status and anthropometric information with SLEEP-50 was done. Data was analysed by SPSS and p<0.05 was considered as statistically significant. Result: Out of 255 subjects 236 provided complete information. 80% students admitted having at least one sleep disorder. Majority of subjects reported to have narcolepsy (65.3%), followed by nightmares (31%), and restless leg syndrome (20.3%). Respondents experiencing nocturnal disturbances, such as phone ringers or vibrating modes, and prolonged engagement with social media were found to be more predisposed to poor sleep quality. Among these 47 respondents, 90.9% of Tobacco users, 96.7% of Alcohol users, and 83.3% of other types of substance abusers reported experiencing sleep disorders compared to their counterparts. Conclusion: The study confirmed that poor sleep is prevalent in medical students. The study suggests that research should focus on improving general sleep education for medical students, identifying at-risk students, and implementing programs to improve sleep.